Popular beliefs regarding the treatment of senile cataract Concepções populares do tratamento da catarata senil - Edméa Rita Temporini; Newton Kara Junior; Newton Kara José; Nilo Holzchuh (Universidade de São Paulo, 2002)
OBJECTIVE: To identify popular beliefs regarding the treatment of senile cataract in patients enrolled in the community health programs on eye rehabilitation. METHODS: A cross-sectional survey was carried out using an interview questionnaire that was applied to 776 subjects drawn from a non-probabilistic sample in five cities of the state of São Paulo. The sample was made up of 47.2% males and 52.8% females, aged 50 to 96 years (average age 71.6 years). RESULTS: Of the total of subjects studied, 41.9% had never attended school, and 78.5% were no longer in the employment market. Most (85.1%) credited the sight restoration to cataract surgery. Among those unconvinced, 47.4% asserted that sight restoration depended only on God's will. A greater proportion of women than men (p 0.0000) believed in the association of cataract and menopause, maternity, and menstrual periods and they admitted using herbal and rose teas for treating cataract. CONCLUSIONS: Misbeliefs related to the causes and treatment of senile cataract were identified, most probably of sociocultural basis, indicating the need of education on the subject. OBJETIVO: Identificar concepções populares em relação ao tratamento de catarata senil entre pacientes atendidos em projetos comunitários de reabilitação visual. MÉTODOS: Em cinco municípios do Estado de São Paulo, Brasil, foi realizado estudo transversal aplicando-se questionário, por entrevista, a uma amostra não-probabilística composta por 776 sujeitos. A amostra foi formada por indivíduos do sexo masculino (47,2%) e do sexo feminino (52,8%), com idade entre 50 e 96 anos, média de 71,6 anos. RESULTADOS: Do total dos sujeitos estudados, 41,9% nunca estudaram, e 78,5% não exerciam mais atividades profissionais. A maioria declarou confiar em resultados de cirurgia de catarata (85,1%); entre os que mostraram dúvida, 47,4% disseram achar que a cura da catarata dependia apenas da vontade de Deus. As mulheres acreditavam, mais do que os homens (p£0,0000), na relação entre menopausa, maternidade, menstruação e ocorrência da catarata. Admitiram usar chás de ervas e de rosas para seu tratamento. CONCLUSÕES: Foram identificadas concepções falsas, de provável origem sociocultural, a respeito de causas e tratamento da catarata senil que indicam a necessidade de intervenções educativas em saúde ocular.